THE EFFECT OF IMPROVING THE QUALITY OF AGRICULTURAL PRODUCTS ON ENSURING THE ECONOMIC SECURITY OF THE ENTERPRISE - VLASENKO, Tetiana; Larina, ТETIANA; STEPANENKO, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Ensuring the economic security of the enterprise plays a significant role in its functioning in general. The implementation of an effective mechanism of economic security of the enterprise requires due attention from the managers to the issues of the level of integration into the global information space, the economic interests of the company, the level of expenditure of corporate resources and a clear organization of activities. The basis of the mechanism of the process of ensuring economic security is a systematic combination of certain tools, methods, means and the information and analytical process of provision, created on the basis of objectively existing principles of the process of ensuring economic security, as well as those formulated by subjects of economic security management of the enterprise for achieving and protecting his financial interests. Currently, the problem of quality improvement is becoming the main criterion for improving the quality of life, socio-economic, foreign economic, political, and environmental security. The concept of product quality is compared with competitiveness, having a general sphere of formation and manifestation. If the competitiveness of enterprises is not increased, the development of both the economy of the state as a whole and its individual regions is impossible. The competitiveness of an agribusiness enterprise depends on the ability of a specific producer to produce a competitive product, the consumer and quality characteristics of which, compared to similar products, determine its market success both on the domestic and foreign markets. The problem of quality assurance is one of the most significant socio-economic problems of the modern world, and the sphere of agriculture is no exception. The company's survival potential, as well as its stable position on the market, is determined by the level of competitiveness, which, in turn, depends on a dozen factors, but primarily on the level of prices and product quality. In the modern world, product quality comes first, leaving behind labor productivity, as well as saving all kinds of resources
Keywords: product quality; competitiveness; economic security; agrarian sphere; products